Statins Mitigate Stress-Related Vascular Aging and Atherosclerosis in apoE-Deficient Mice Fed High Fat-Diet: The Role of Glucagon-Like Peptide-1/Adiponectin Axis - Lei, Yanna; Cui, Qingsong; Yang, Guang; Piao, Limei; Inoue, Aiko; Wu, Hongxian; Li, Xiang; Kuzuya, Masafumi; Cheng, Xian Wu (Frontiers in Cell and Developmental Biology, 2021)
ABSTRACT Objectives: Exposure to chronic psychosocial stress is a risk factor for atherosclerotic cardiovascular diseases. Given that the 3-hydroxy-3-methylglutaryl-coenzyme reductase inhibitor statins prevent atherogenesis, we evaluated whether pitavastatin prevents chronic stress- and high fat diet-induced vascular senescence and atherogenesis in apolipoprotein E-deficient (ApoE−/−) mice, with a special focus on glucagon-like peptide-1 (GLP-1)/adiponectin (APN) axis. Methods and Results: 6-week-old ApoE−/− mice loaded a high-fat diet were randomly assigned into non-stress (n=12) and stress (n=13) groups for 12 weeks. Non-stress control mice were left undisturbed. Chronic stress accelerated high fat diet-induce arterial senescence and atherosclerotic plaque growth. The chronic stress lowered the levels of circulating GLP-1 as well as adipose and plasma APN. As compared with the stress alone mice, the pitavastatin-treated mice had reduced macrophage infiltration, elastin fragments, and increased plaque collagen volume, and lowered levels of osteopontin, toll-like receptor-2/-4, macrophage chemoattractant protein-1, C-X-C chemokine receptor-4, p47phox, p47phox, gp91phox, cathepsins S, p16, and p21, mRNAs and/or proteins. Pitavastatin increased plasma GLP-1 and APN levels and suppressed matrix metalloproteinase-2/-9 gene expressions and activities in the aortas. Finally, the protective effect of pitavastatin was abrogated by APN blocking. Conclusions: These findings suggested that the piatavastatin-mediated pleiotropic vasculoprotective effects are likely attributable, at least in part, to the elevation of GLP-1 and APN levels and the inhibition of diet-induced plaque inflammation, oxidative stress, and proteolysis in ApoE−/− mice received chronic stress conditions. Keywords: chronic stress, atherosclerosis, statin, inflammation, adiponectin